Effects of smartphone-based collaborative vlog projects on EFL learners’ speaking performance and learning engagement - Huang, Hui-Wen (Australasian Journal of Educational Technology, 2021)
This study examined how smartphone-based collaborative video projects influenced English as a Foreign Language (EFL) learners’ speaking performance and learning engagement using blended learning in China. The collaborative video projects helped students engage in two smartphone-based video filming tasks to combine language learning with real-life experiences simultaneously. A total of 65 college students used smartphones to participate in 3-minute collaborative video tasks that were related to the learning context of the classroom textbook. Qualitative and quantitative data were collected during this 8-week intervention. This included pretest and post-test speaking scores, a questionnaire on group collaboration, students’ final reflections and focus group interviews. A paired-sample t test, descriptive analysis and qualitative content analysis were used to analyse the data. The results indicate that students’ speaking abilities were significantly improved at the end of the intervention. They enjoyed group collaboration in the video projects and appreciated acquiring digital media production skills. Interview results highlight the opportunities for and challenges of the educational application of video projects in EFL classrooms. Implications for practice or policy: Integrating collaborative vlog projects in EFL classrooms can stimulate students’ speaking performance. Student-made collaborative vlogs can help students develop 21st century skills, especially in digital media production. Smartphone-based vlog projects can increase learners’ engagement and enhance their group collaboration skills.